Molecular mechanism of stevioside on tnf-α-induced insulin resistance in 3T3-L1 adipocytes by integration of metabolomics, protein and gene expression / Norhisham Haron - Haron, Norhisham (2023)
The increasing prevalence of insulin resistance (IR) and T2DM provides compelling evidence for the identification of novel biomarkers, molecular targets and the development of effective drugs to prevent and treat the disease. Stevioside (SVS), the main constituent of Stevia rebaudiana Bertoni, has several therapeutic effects for metabolic syndrome, including lowering blood pressure, reducing blood glucose levels, potentiating insulin secretion and improving insulin sensitivity. However, the molecular basis underlying the antidiabetic effect of SVS on metabolic changes and pathways of insulin resistance is unknown. Therefore, the aim of this study was to investigate the metabolome response of SVS in a cell culture model of insulin resistance using metabolomics, protein and gene expression analyses. 3T3-L1 adipocyte cells were stimulated with 1.0 ng/mL TNF-α for insulin resistance and treated with SVS or rosiglitazone maleate (RM). The cell lysate was harvested and analysed by liquid chromatography-mass spectrometry-quadrapole time-of-flight analysis (LC/MSQTOF).